Pengaruh Social Media Marketing Instagram dan Brand Image terhadap Loyalitas Konsumen Richeese Factory - Shafa Ismananti, Elvira Diva (Jurnal Dimamu, 2025)
The growth of internet users in Indonesia is always increasing, especially internet users in the form of social media which in real-time and without limits can connect between people or groups in a social-based platform. Social media is also an effective sales promotion support tool in achieving sales targets. In addition to promotion, Brand Image or brand image as a form of identity of the products offered to customers. So that these two things might affect consumer loyalty. This phenomenon certainly makes business people, especially food business businesses that have been established since several years ago such as Richeese Factory, have to adjust their promotional strategies to follow people's habits so that the corporate identity that has been built can still exist today. This study aims to determine the effect of Social Media Marketing Instagram, and Brand Image on Richeese Factory consumer loyalty. The approach taken in the research is the Quantitative method. The sample in this study were 100 respondents obtained from followers of the @richeese_factory Instagram account where the data collection was carried out by distributing questionnaires via Google Forms, with the independent variables in this study, namely Social Media Marketing Instagram (X1), and Brand Image (X2), then the dependent variable is Loyalty (Y). Data processing is done through the SPSS 25 application. The results of this study are that Social Media Marketing Instagram and Brand Image has a positive significant effect on consumer loyalty.